Small-scale constructed wetland for onsite light grey water treatment and recycling - Kadewa, Wilfred William (Cranfield University, 2010)
This study focused on the investigation of the impact of household cleaning and personal care products on the quality of grey water and the assessment and optimisation of grey water treatment by a novel constructed wetland design. The prototype wetland design which comprised three-stage cascading beds (0.27 m 2 by 0.20 m deep) with sand media, (d10: 1.0 mm and d90: 4.0 mm) was tested for treatment performance to meet non-potable reuse standards in three versions, unplanted open beds, unplanted covered beds, and planted beds (comprising mixtures of Iris pseudacorus, Iris chrysographes, Carex elata Aurea and Mentha aquatica). The prototypes were benchmarked against a standard single-pass wetland (6 m 2 by 0.7 m) planted with Phragmites australis. Performance was measured in terms of removal of conventional water quality determinant parameters, as well as Total coliforms and E coli, and surfactants. Microbial dynamics were also monitored during the study by looking at variations in microbial compositions with time for the different wetlands. All the wetland versions effectively removed more than 98 % turbidity and organics meeting the most stringent reuse wastewater reuse standards of < 2.0 NTU and < 10 mg BOD5/L respectively. The influent grey water had low BOD:COD ratio ranging from 0.27 – 0.45, which is indicative of low biodegradability. The comparison of the cascade wetland performances showed the following: open beds > planted = covered, with the open beds version meeting reuse standards virtually throughout the monitoring period, despite recurrence of schmutsdecke in the top bed. All wetland technologies supported viable populations of microorganisms. Only phospholipid fatty acids (PLFAs) of lower carbon chain length (< C20) had concentrations greater than 1 mol %, in all the wetlands beds, confirming that the majority of the PLFAs in the media were from contribution of microbial organisms and not plant organic matter. Characterisation of microbial organisms was carried out to understand the constructed wetlands functioning and thus the treatment processes. The household products showed nutrient deficiency signifying low treatability. Product branding did not show correlation with any water quality parameters. In terms of toxicity, laundry and cleaning products were more inhibiting to soil microorganisms than were personal care products.
Keywords: grey water; cleaning products; vertical flow wetland; water reuse; water quality